Evaluación del momento óptimo de cosecha de cuatro variedades de arroz (Oryza sativa) al trasplante en el Bajo Mayo - Paredes Flores, Demóstenes (2001)
In order to determine the optimal harvest time of four varieties of rice crop in five seasons and their effect on the millers and grain edibility an experiment was conducted at the Experimental Station "El Porvenir" located at Km 14.5 Marginal Highway South Tarapoto - Juanjui, in clay soil irrigated transplantation between February and July 2000. the challenge of divided plot completely randomized block design with three replications; varieties, Capirona, Selva Alta, Inia 501 Bijao and Line CT 10310 were considered as the main plots and harvest times as subplots. The variety Inia 501 Bijao had the highest percentage of whole grain, up 60% when it was harvested between 30 to 35 after 50% flowering and high jungle variety with the lowest percentage above 51% in harvesting the 35 days after 50% flowering. No significant statistical difference between the yields of the varieties evaluated (7,303,7,531 and 7,587 t / ha) were found when they were harvested at 40,45, and 50 days after 50% flowering. Edibility tests showed that variety is the determining factor of the gelatinization temperature and between harvest times no statistically significant differences were found each other. Varieties (Capirona, High Forest and Line CT 10310) present temperature of Middle / High gelatinization and variety Inia present temperature of 501 Bijao Middle / Low gelatinization. Treatment Selva Alta - 50 days after 50% flowering reached the cost-benefit ratio lower with 46.70% and Linea treatment CT10310-30 days after 50% flowering I report the highest value with 65.90%